2016
DOI: 10.4337/ejeep.2016.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Making the euro viable: the Euro Treasury Plan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Applying this general approach to the Eurozone could either aim at a relevant federal EU budget with a EU/Eurozone fiscal authority issuing debt, which will then be accepted by the ECB as collateral, as for example proposed by Bibow (2016). However, this would require major institutional changes, which might be difficult to obtain in the short to medium run.…”
Section: A Kaleckian/post-keynesian Policy MIX For the Eurozonementioning
confidence: 99%
“…Applying this general approach to the Eurozone could either aim at a relevant federal EU budget with a EU/Eurozone fiscal authority issuing debt, which will then be accepted by the ECB as collateral, as for example proposed by Bibow (2016). However, this would require major institutional changes, which might be difficult to obtain in the short to medium run.…”
Section: A Kaleckian/post-keynesian Policy MIX For the Eurozonementioning
confidence: 99%
“…It needs to overcome the monetary-fiscal 'divorce' and establish a central monetaryfiscal axis of power instead. My 'Euro Treasury' proposal (Bibow 2013;2014;2015;2019a;2019b) provides a straightforward solution to the latter systemic deficiency.…”
Section: Concluding Observationsmentioning
confidence: 99%
“…Diaz del Hoyo, Dorrucci, Heinz, and Muzikarova (2017), Zuk, Polgár, Savelin, Diaz del Hoyo, and König (2018), Arestis (2016), Bibow (2016) concluded that the temporary fulfilment of the numerical convergence criteria set in the Maastricht Treaty was not, in itself, a guarantee of smooth membership in the euro area (see further details of the Maastricht Treaty in Section 2.1). A holistic approach and the integration of all dimensions of sustainable economic convergence -be these real, nominal or institutional in nature -is, therefore, required.…”
Section: Introductionmentioning
confidence: 99%